ANALYSIS OF IMMUNITY IN OSTEOSARCOMA AS A BASIS FOR DEVELOPMENT FOLLOWING THERAPY - Ferdiansyah Mahyudin; Mouli Edward; Muhammad Hardian Basuki; Kadek Seta Prawira (Journal Orthopaedi and Traumatology Surabaya)
Background: Osteosarcoma is a malignant bone disease. Predictors which used to determine osteosarcoma from non-invasive (stage IIB) to invasive (stage III), through the ratio of macrophages-1 (M-1) which are pro-inflammatory (anti-cancer) with macrophages-2 (M-2) which have anti-inflammatory characteristic (pro cancer) is not clear yet.